Lithuania - Lerner Publications Company. Geography Dept. (Minneapolis : Lerner Publications Co., 1992)
Text and accompanying photographs discuss Lithuania's geography, ethnic mixture, history, political events, economic activities, environmental hazards, relations with neighbors, and future.
Includes index and glossary.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.1
4-6
Keywords: Lithuania -- Juvenile literature; Lithuania; Lithuania